Practical variable speed drives and power electronics - Barnes, Malcolm (Oxford ; Burlington, MA : Newnes, 2003)
Typical practical applications of VSDs in process control and materials handling, such as those for pumping, ventilation, conveyers, compressors and hoists are covered in detail.?Provides a fundamental understanding of the installation, operation and troubleshooting of Variable Speed Drives (VSDs)?Includes practical coverage of key topics such as troubleshooting, control wiring, operating modes, braking types, automatic restart, harmonics, electrostatic discharge and EMC/EMI issues?Essential reading for electrical engineers and those using VSDs for applic.
Cover; Frontmatter; 1. Introduction; 2. 3-Phase AC induction motors; 3. Power electronic converters; 4. Electromagnetic compatibility (EMC); 5. Protection of AC converters and motors; 6. Control systems for AC variable speed drives; 7. Selection of AC converters; 8. Installation and commissioning; 9. Special topics and new developments; Appendix A: Motor protection -- direct temperature sensing; Appendix B: Current measurement transducers; Appendix C: Speed measurement transducers; Appendix D: International and national standards.
Includes "Glossary of common terms used with AC variable speed drives" (p. [266]-276) and index.
Keywords: Variable speed drives; Electronic books